Infiormation-Gap Decision Theory : Decision Under Severe Uncertainty - Ben-Haim, Yakov (New york Academic Press, 2001)
This text presents a theory of decision-making under severe uncertainty. It begins with a discussion of info-gap models of uncertainty. This is followed by an approach to the quantification of severe lack of information.
Include Author and Subject Index
Keywords: Uncertainty -- Risk assessment--Mathematical models -- Decision making--Mathematical models -- Risk -- Decision making